(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the modern world, the problem of the negative attitude of university students to physical education is of growing interest. Such an attitude and unwillingness to attend classes causes a deterioration in the health of students, which leads to a decrease in academic performance. In the study, we prove the existence of this problem, consider the reasons for the negative attitude towards physical education and offer ways to solve the problem under study. We have found that a student’s attitude to physical education depends not only on how productive and fruitful this activity is for him, but also on the student’s fatigue and the time when the lesson is held.